Developments in the first year of a resilience-focused program for health care workers. (December 2021) - DePierro, Jonathan; Marin, Deborah B.; Sharma, Vansh; Costello, Zorina; Starkweather, Sydney; Katz, Craig L.; Lim, Sabina; Charney, Dennis S.
Abstract: The present article comprises a one-year retrospective review of the efforts of the Mount Sinai Center for Stress, Resilience and Personal Growth, an initiative to support the resilience and well-being of health care workers that was founded amid the first peak of the pandemic in New York in 2020. Specific offerings to date have included evidence-backed resilience workshops, a digital health platform, and a specialty screening and treatment service. All services have been modified or expanded in response to changing needs and are subject to ongoing research. Robust evidence-based programming that addressing health care worker well-being, regardless of role, may prove beneficial to institutions well beyond the pandemic.